2008
DOI: 10.1111/j.1365-2826.2008.01669.x
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Alcohol Exposure: Foetal Programming, the Hypothalamic‐Pituitary‐Adrenal Axis and Sex Differences in Outcome

Abstract: Prenatal exposure to alcohol has adverse effects on offspring neuroendocrine and behavioural functions. Alcohol readily crosses the placenta, thus directly affecting developing foetal endocrine organs. In addition, alcohol‐induced changes in maternal endocrine function can disrupt the normal hormonal interactions between the pregnant female and foetal systems, altering the normal hormone balance and, indirectly, affecting the development of foetal metabolic, physiological and endocrine functions. The present r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
263
2
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 285 publications
(288 citation statements)
references
References 210 publications
15
263
2
5
Order By: Relevance
“…Prenatal ethanol exposure is known to influence the activity of the hypothalamic-pituitary-adrenal axis and to result in elevated maternal glucocorticoid levels. 40 Thus it is plausible to suggest that the findings observed within this study may be mediated at least in part by the actions of glucocorticoids.…”
Section: Discussionmentioning
confidence: 75%
“…Prenatal ethanol exposure is known to influence the activity of the hypothalamic-pituitary-adrenal axis and to result in elevated maternal glucocorticoid levels. 40 Thus it is plausible to suggest that the findings observed within this study may be mediated at least in part by the actions of glucocorticoids.…”
Section: Discussionmentioning
confidence: 75%
“…Alcohol consumed by the mother can easily pass through the placenta, directly affecting the developing fetus. In addition, alcohol can also indirectly affect the fetus by impacting the mother's critical hormonal balance and placental function [11,12,71]. The developing brain is particularly vulnerable to the toxicological effects of alcohol.…”
Section: Alcoholmentioning
confidence: 99%
“…Alcohol is known to increase maternal levels of glucocorticoids (Liang et al, 2011, Weinberg et al, 2008 and have previously been shown to decrease placental mRNA levels of 11βHsd2 in mice (Liang et al, 2011). While contradictory to our findings, the mRNAs in the study of Liang et al (2011) were analysed in animals receiving very high doses of alcohol administration (40% EtOH v/v).…”
Section: Pc:etoh-exposure Impaired the Placental Glucocorticoid Barriercontrasting
confidence: 99%
“…Alcohol crosses the placenta and can directly affect the fetus, or provoke changes in maternal endocrine functions that secondarily can interfere with fetal development and cause metabolic, physiological and endocrine disruptions -or result in miscarriage (Weinberg et al, 2008). Alcohol-induced birth defects may be established before the woman is aware of her pregnancy , therefore women drinking both before pregnancy confirmation and during pregnancy are at risk of delivering a baby with fetal alcohol spectrum disorder (FASD) (Abel, 1999).…”
Section: The Effect Of Alcohol On the Fetus And Fetal Alcohol Syndromementioning
confidence: 99%